A channel allocation method based on dual-population differential evolution in wireless sensor networks. (25th May 2021) - Cao, Yu; Wei, Wei; Pei, Huiting
To solve the problem of low-efficiency channel allocation due to the high density of nodes in traditional wireless sensor networks (WSNs), a channel allocation method based on dual-population differential evolution is proposed. In our paper, the crossover and mutation operations of the differential evolution algorithm are analysed; multichannel mutation crossover optimisation is proposed by combining a differential evolution algorithm with a dual-population search method. Anti-interference optimisation is carried out for different network levels with a certain capacity, considering the time slot parameter interference degree, link capacity, and multichannel cross-layer analysis. According to the multichannel mutation cross-optimisation method, the constraint conditions are determined, the channel is divided, and a linear membership function is constructed to perform channel allocation. The experimental results show that when the mutation parameter and crossover probability of two-population differential evolution are 0.1 and 0.6, respectively, the channel allocation efficiency of the proposed method is the highest, and the shortest channel allocation time is 3.4 s.